Tissue Factor-Expressing Tumor-Derived Extracellular Vesicles Activate Quiescent Endothelial Cells via Protease-Activated Receptor-1 - Che, Sara P. Y.; Park, Jeannie Y.; Stokol, Tracy (Frontiers in Oncology, 2017)
Tissue factor (TF)-expressing tumor-derived extracellular vesicles (EV) can promote metastasis and pre-metastatic niche formation, but the mechanisms by which this occurs remain largely unknown. We hypothesized that generation of activated factor X (FXa) by TF expressed on tumor-derived EV could activate protease-activated receptors (PAR) on non-activated endothelial cells to induce a pro-adhesive and pro-inflammatory phenotype. We obtained EV from TF-expressing breast (MDA-MB-231) and pancreatic (BxPC3 and Capan-1) tumor cell lines. We measured expression of E-selectin and secretion of interleukin-8 (IL-8) in human umbilical vein endothelial cells after exposure to EV and various immunologic and chemical inhibitors of TF, FXa, PAR-1 and PAR-2. After 6 hours of exposure to tumor-derived EV (pretreated with FVIIa and FX) in vitro, endothelial cells upregulated E-selectin expression and secreted IL-8. These changes were decreased with an anti-TF antibody, FXa inhibitors (FPRCK and EGRCK), and PAR-1 antagonist (E5555), demonstrating that FXa generated by TF-expressing tumor-derived EV was signaling through endothelial PAR-1. Due to weak constitutive PAR-2 expression, these endothelial responses were not induced by a PAR-2 agonist peptide (SLIGKV) and were not inhibited by a PAR-2 antagonist (FSLLRY) after exposure to tumor-derived EV. In conclusion, we found that TF-expressing cancer-derived EV activate quiescent endothelial cells, upregulating E-selectin and inducing IL-8 secretion through generation of FXa and cleavage of PAR-1. Conversion of resting endothelial cells to an activated phenotype by TF-expressing cancer-derived EV could promote cancer metastases.